Structure Selection Technique of Multi-Processor Computing Systems - Kovalenko, S.M.; Petushkov, G.V.; Platonova, O.V. (International Journal of Engineering and Technology, 2018)
This paper discusses construction of modern microprocessor structures and computing modules, including microprocessors and RAM, as well as computing systems containing computing modules combined by network means. Â Also, the "overhead" expenditure of time used for data transmission in the considered subsystems is analyzed. Estimates of the time spent on calculations and data exchange in multiprocessor computing systems (VS) are considered. Â An expression is derived for estimating the optimal number of computational modules in an aircraft that provides the minimum program execution time. Implementation of an aircraft with the structure recommended in the work, allows us to increase the overall performance of the system when performing the tasks that require intensive data exchange between individual computing modules. The results of research are expected to be used in the design and development of high-performance aircraft structures.